From flint provenance to mobility studies: New raw material determinations from Late Neolithic wetland sites at Lake Biel and Lake Constance. (30th March 2022) - Affolter, Jehanne; Emmenegger, Lea; Hafner, Albert; Heitz, Caroline; Hinz, Martin; Stapfer, Regine; Wehren, Helena
Abstract: The aim of this paper is twofold: first, we strive to find routes of flint supply that may have been used systematically on the northern Alpine Foreland during the fourth millennium BCE, based on the origin of the siliceous raw materials; second, these routes will be interpreted as a part of cultural entanglements. Using the sedimentary microfacies method for sourcing the raw materials of artefacts recovered in prehistoric sites makes it possible to study the provenances of large series' pieces in a non-destructive manner. Besides insights into the economy of flint raw material supply practices of single precisely-dated sites, this cross-regional comparison allows us to gain a deeper understanding of the economic relations and thus the mobility pattern of the respective settlement communities in different time periods. The method used for raw material sourcing is described in Affolter et al., 2021 (this issue) in detail. In this paper, we present as a first research step new raw material determinations from four Late Neolithic wetland sites on the northern Alpine Foreland that encompass several dendrochronologically-dated settlements: Twann Bahnhof (3838–3532 BCE) and Sutz-Lattrigen Hauptstation innen/Hafen (3827–3566 BCE) at Lake Biel and Hornstaad Hörnle IA (3919–3902 BCE) as well as Sipplingen Osthafen A and B (3919–3904 and 3857–3817 BCE) at Lake Constance. Thanks to the precise dating of the settlements and the finds deriving from the respective stratigraphic layers, not only regional differences but also transformations over time in raw material supplies can be approached with an extraordinarily high temporal resolution. Hence, this article demonstrates the interpretative potential of flint provenance determination to study the spatial mobility of prehistoric settlement communities. In addition to the presentation of previously unpublished materials, the aim here is to show an initial approach to the study of spatial mobility and entanglements using flint data, which is to be expanded in the future.